The Milk Supply of Paris, Rome and Berlin - Bacon, Lois B.; Cassels, John M. (Quarterly Journal of Economics, 1937)
Introduction, 626. — Paris, 627. — The price-making forces, 630. — The surplus problem, 631. — Rome, 633. — The Fascist organization, 635. — Use of a base-rating plan, 637. — Berlin, 638. — Optional cartellization, 1930–34, 639. — Compulsory cartellization since 1933, 643. — Conclusion, 647.